Mecro‐Economic Voting: Local Information and Micro‐Perceptions of the Macro‐Economy. (5th June 2014) - Ansolabehere, Stephen; Meredith, Marc; Snowberg, Erik
<x xml:space="preserve">Abstract</x> We develop an incomplete information theory of economic voting, where voters' information about macro‐economic performance is determined by the economic conditions of people similar to themselves. We test our theory using both cross‐sectional and time‐series survey data. A novel survey instrument that asks respondents their numerical assessment of the unemployment rate confirms that individuals' economic information responds to the economic conditions of people similar to themselves. Furthermore, these assessments are correlated with individuals' vote choices. We also show in time‐series data that state unemployment robustly correlates with evaluations of national economic conditions, and presidential support.